(untitled) (Research, Society and Development, 2022)
Mental health is an essential part of human life. Having a satisfactory mental health is fundamental for a quality health as a whole. With the pandemic of COVID-19 and the consequent restriction of usual activities, several problems were perceived, such as: anxiety, depression, panic attacks, and stress. When we talk about the professionals who act in the front line of the pandemic, it is believed that the incidence is even higher due to the responsibility of treating the contaminated patients, especially that in the beginning, because there were no studies, treatment options, vaccines, conducts and protocols to be used. Depression, although underdiagnosed, is an incapacitating disease and, when it affects public employees who work in primary health care units, it makes their work even more exhausting, leading to a possible prejudice to the conduct and management of the cases, being a problem for public health. In this present study, a survey was carried out using a validated questionnaire (PQH-9) to verify the percentage of public health workers who have depression in their various degrees, and of these, more than half of the interviewees (54%) have some degree of depressive disorder, with the objective of the data collected serving to draw the attention of professionals and managers to the subject, since depression is a highly prevalent and underdiagnosed disease, especially when it requires proper care.